Water absorption and dormancy-breaking requirements of physically dormant seeds of Sophora tomentosa L. and Erythrina speciosa Andr. (Fabaceae-Faboideae) - Luzia Delgado, Carolina Maria (Universidad de Costa Rica, 2015)
Water absorption and dormancy-breaking requirements of physically dormant seeds of Sophora tomentosa L. and Erythrina speciosa Andr. (Fabaceae-Faboideae) Carolina Maria Luzia Delgado1, Alexandre Souza de Paula2, Marisa Santos3 and Maria Terezinha Silveira Paulilo4 1-Departamento de Botânica, Universidade Federal de Santa Catarina, Florianópolis, 88040-900, Brazil; delgado_carol@yahoo.com.br2- Departamento de Botânica, Universidade Federal de Santa Catarina, Florianópolis, 88040-900, Brazil; alexandredepaula_07@hotmail.com3- Departamento de Botânica, Universidade Federal de Santa Catarina, Florianópolis, 88040-900, Brazil; marint@mbox1.ufsc.br4- Departamento de Botânica, Universidade Federal de Santa Catarina, Florianópolis, 88040-900, Brazil; paulilo@ccb.ufsc.br